Cross border litigation in Islamic banking and finance - Jalil, Md. Abdul; Ansari, Abdul Haseeb (2010)
Islamic banks in the world are performing very well in the financial market. They are complying with Shar‘ah requirements while investing money in business. Nowadays, they are also investing money in foreign countries. This is known as cross border transaction. There is some risk and litigation problems in cross border transactions. If any dispute arises out of a cross border transactions, it should be referred to a court or an arbitration centre. Now the issue is which country’s court or arbitration centre will have jurisdiction to hear the dispute and give a decision or award? Another problem that may arise in cross border litigation is that of conflict of laws and choice of law issues. The parties involved in a contract are from different countries. The applicable laws might be substantially different between the countries. In that situation the question of which country’s law should be applied to solve the dispute is a complicated issue. When conflict of laws and conflict of jurisdictions are involved, another related legal issue may arise regarding enforcement of foreign judgments. In this paper these issues have been critically addressed and pragmatic suggestions have been offered.